Recent Developments in the Functionalization of Betulinic Acid and Its Natural Analogues: A Route to New Bioactive Compounds - Joana L. C. Sousa (Molecules, 2019)
Betulinic acid (BA) and its natural analogues betulin (BN), betulonic (BoA), and 23-hydroxybetulinic (HBA) acids are lupane-type pentacyclic triterpenoids. They are present in many plants and display important biological activities. This review focuses on the chemical transformations used to functionalize BA/BN/BoA/HBA in order to obtain new derivatives with improved biological activity, covering the period since 2013 to 2018. It is divided by the main chemical transformations reported in the literature, including amination, esterification, alkylation, sulfonation, copper(I)-catalyzed alkyne-azide cycloaddition, palladium-catalyzed cross-coupling, hydroxylation, and aldol condensation reactions. In addition, the synthesis of heterocycle-fused BA/HBA derivatives and polymer‒BA conjugates are also addressed. The new derivatives are mainly used as antitumor agents, but there are other biological applications such as antimalarial activity, drug delivery, bioimaging, among others.